GAMBARAN KESEJAHTERAAN DIGITAL SISWA DI SEKOLAH INDONESIA JEDDAH TINGKAT SMA - Nurmalahayati; Setyawati, Denok; Naqiah, Najatun; Indah Pratiwi, Titin (IKIP Siliwangi, 2025)
This study aims to describe the level of digital well-being among high school students at the Indonesian School in Jeddah. The study is driven by the high duration of digital device usage among students, influenced by geographical, socioeconomic factors, and lack of parental supervision. A descriptive quantitative approach was used with 54 respondents from grades X and XI. The instrument employed was a digital well-being questionnaire, validated and tested for reliability, covering five core dimensions. Results showed that 43% of students had high digital well-being, 34% moderate, and 23% low. The social interaction aspect scored the highest, while digital safety and self-control require more attention. This study highlights the need for counseling services and digital literacy education in schools to promote healthy and balanced digital habits. The findings can serve as a foundation for policy formulation and school-based interventions to foster a positive digital culture among students.